Segmentasi Pemilih Pemula berdasarkan Akses Berita Politik Melalui Media Sosial di Kabupaten Bogor - Roni Jayawinangun; David Rizar Nugroho (Jurnal Komunikasi Pembangunan, 2019)
Political participation is an important problem because it is one form of support that comes from various parties or groups. Political participation is inseparable from the media as a means of information for the community. Beginner voters are one part of the community whose voice is needed in the political process. Beginner voters with media are two things that cannot be separated, especially the use of social media. The research objective consists of several things, namely: 1). Knowing the characteristics of beginner voters in Bogor Regency; 2). Knowing the use of social media in accessing political news on beginner voters; 3). Analyzing the political typology of beginner voters; 4). Analyzing the segmentation of beginner voter typology based on access to political news on social media. This study used a survey approach and data collection using a questionnaire on 105 respondents. The sampling method uses quota sampling while the data analysis uses descriptive analysis, mean scores and CHAID. The results of this study indicate that the characteristics of beginner voters in Bogor Regency are dominated by women, high school education, not participating in the organization. Instagram is the most widely used social media as access to political news. The typology of beginner voters from the largest percentage is apathetic voters followed by naive, alienated and loyal voters, the media, the more access to news through social media encourages voters to be loyal, without accessing politics through social media makes voters apathetic.